Verbal bullying in the school environment: A literature-based analysis of teachers' strategies - Rahayu, Nina; Wulandari, Febriyantika; Arif, Muhammad; Afrida, Nina; Nadila, Nadila (Jurnal Anifa: Studi Gender dan Anak, 2025)
Many primary school students continue to experience or engage in bullying at school, particularly verbal bullying such as insults and teasing. This behavior negatively impacts students' psychological well-being and learning processes. Teachers play a crucial role in preventing bullying through effective learning strategies and character education. This study aims to analyze teachers' strategies in addressing verbal bullying using a literature review approach. The findings indicate that effective strategies include: early identification of bullying behavior, implementation of anti-bullying programs, and reinforcement of core values such as empathy and responsibility, and strong classroom management. In addition, educational sanctions serve as an important deterrent. These strategies are essential in creating a safe and supportive learning environment for all students.